S49 Dupilumab improves lung function across baseline disease characteristics in patients with evidence of type 2 inflammation at baseline: the LIBERTY ASTHMA QUEST study. (12th November 2019) - Paggiaro, P; Castro, M; Canonica, WG; Douglass, JA; Tohda, Y; Rice, MS; Deniz, Y; Rowe, P; Amin, N; Teper, A
Abstract : Introduction: Dupilumab, a fully human VelocImmune®-derived monoclonal antibody, blocks the shared receptor component for interleukin (IL)-4/IL-13, key drivers of type 2 inflammation in multiple diseases. In the phase 3 LIBERTY ASTHMA QUEST study (NCT02414854 ), add-on dupilumab 200 mg/300 mg every 2 weeks (q2w) vs placebo reduced severe exacerbations and improved pre-bronchodilator forced expiratory volume in 1 second (FEV1 ) in patients with uncontrolled, moderate-to-severe asthma. Treatment effects were greater in patients with elevated type 2 biomarkers at baseline. This post hoc analysis assessed the effects of dupilumab on pre-bronchodilator FEV1 by baseline disease characteristics in patients with baseline levels of blood eosinophils ≥150 cells/µL or fractional exhaled nitric oxide (FeNO) ≥20 ppb, biomarkers of type 2 inflammation.  Methods: Least squares (LS) mean changes from baseline to Week 12 in pre-bronchodilator FEV1 were assessed using mixed-effect models with repeated measures. Results: Dupilumab 200 mg/300 mg q2w vs placebo improved pre-bronchodilator FEV1 in patients with elevated type 2 biomarkers in subgroups defined by controller medications at randomization, baseline pre-bronchodilator FEV1 (≤1.75 L/>1.75 L), number of severe asthma exacerbations (≥1, ≥2, ≥3) in the previous year, smoking history (never smoked/former smoker with a smoking history ≤10 pack-years), and age at asthma onset (≤40 years/>40 years) (figure). The effect of dupilumab was significant in all subgroups except for a couple of subgroups of patients with type 2 inflammation on triple asthma controllers and those who were former smokers. Overall, the most frequent dupilumab 200 mg/300 mg vs matched placebo adverse event was injection-site reaction (15%/18% vs 5%/10%). Conclusions: Dupilumab significantly improved pre-bronchodilator FEV1 across most baseline disease characteristics in patients with uncontrolled, moderate-to-severe asthma with evidence of type 2 inflammation at baseline. Dupilumab was generally well tolerated.